The African National Congress and the Regeneration of Political Power - Booysen, Susan; Project Muse. (Johannesburg : Wits University Press, 2011)
The ANC is a party-movement that draws on its liberation credentials yet is conflicted by a multitude of weaknesses, factions and internal succession battles. Booysen constructs her analysis around the ANC's four faces of political power - organisation, people, political parties and elections, and policy and government - and explores how, since 1994, it has acted to continuously regenerate its power.
Introduction : ANC pathways to claiming, consolidating and regenerating political power -- Aluta continua, from Polokwane to Mangaung -- The ANC and its pillars of people's power -- Power through the ballot and the brick -- Participation and power through co-operation, complicity, co-optation -- Power through elections: serial declines, but the centre holds -- Floor-crossing and entrenchment of ANC electoral supremacy -- Subjugation and demise of the (new) National Party -- Countered and cowered Congress of the People (Cope) -- State institutions as site of struggle in ANC wars -- Between centralisation and centralism : the Presidency of South Africa -- Policy, pursuit of the 'turn to the left' and the paradox of continuity -- ANC at a critical conjuncture : movement, people, elections, governance.
In English.
Description based on print version record.
Keywords: African National Congress; African National Congress; Power (Social sciences); Politics and government; POLITICAL SCIENCE -- Political Ideologies -- Democracy; POLITICAL SCIENCE -- General; Politics and government; Society and social sciences Society and social sciences; Pouvoir (Sciences sociales) -- Afrique; Power (Social sciences) -- Africa; South Africa; Africa; Afrique -- Politique et gouvernement -- 1960-; South Africa -- Politics and government -- 1994-; Africa -- Politics and government -- 1960-; Electronic books